Effect Of Water Regimes And Weed Management Practices On Nutrient Uptake By Rice And Weeds Under The System Of Rice Intensification (Applied Biological Research, 2016)
A field experiment was conducted in kharif 2012 and 2013 at MRCFC,  SKUAST, Khudwani (Kashmir) on a silty clay loam soil to evaluate the  impact of water regimes and weed management practices on nutrient  uptake in rice and weeds under SRI. The soil at experimental site was  neutral in reaction, medium in available P, K and organic carbon and  low in available N. The treatments comprised of 3 irrigations schedules  [alternate wetting and drying (AWD), continuous saturated condition  and continuous flooding] and 7 weed management practices viz., 4  herbicidal treatments [pyrazosulfuron ethyl @ 20 g a.i. ha-1 (3 DAT);  cyhalofop butyl @ 80 g a.i. ha-1 (15 DAT); pyrazosulfuron ethyl 20 g a.i.  followed by cyhalofop butyl 80 g a.i. ha-1 (3 and 15 DAT), and butachlor  @ 1.5 kg a.i. ha-1 (3 DAT)]; cono weeding, weedy check and weed-free  control. The results revealed that saturated water regime treatment had  highest uptake of macronutrients by grain and straw, while highest  uptake of macro-nutrients by weeds was in AWD and lowest in  continuous flooding. Among weed control measures, the lowest  macronutrients uptake by crop was associated with post-emergence  application of cyhalofop-butyl and highest amount of NPK depletion by  weeds was observed in unweeded control. Minimum NPK uptake by  weeds was noticed in sequential application of pyrazosulfuron-ethyl @  20 g a.i. ha-1 and cyhalofop-butyl @ 60 g a.i. ha-1 treatment.
Keywords: SRI; water regimes; nutrient up-take; rice; weeds